Diverse functional outcomes of Plasmodium falciparum ligation of EPCR: potential implications for malarial pathogenesis. (20th July 2015) - Gillrie, Mark R.; Avril, Marion; Brazier, Andrew J.; Davis, Shevaun P.; Stins, Monique F.; Smith, Joseph D.; Ho, May
Summary: P lasmodium falciparum ‐infected erythrocytes (IRBC) expressing the domain cassettes (DC) 8 and 13 of the cytoadherent ligand P. falciparum erythrocyte membrane protein 1 adhere to the endothelial protein C receptor (EPCR). By interfering with EPCR anti‐coagulant and pro‐endothelial barrier functions, IRBC adhesion could promote coagulation and vascular permeability that contribute to the pathogenesis of cerebral malaria. In this study, we examined the adhesion of DC8‐ and DC13‐expressing parasite lines to endothelial cells from different microvasculature, and the consequences of EPCR engagement on endothelial cell function. We found that IRBC from IT4var19 (DC8) and IT4var07 (DC13) parasite lines adhered to human brain, lung and dermal endothelial cells under shear stress. However, the relative contribution of EPCR to parasite cytoadherence on different types of endothelial cell varied. We also observed divergent functional outcomes for DC8 cysteine‐rich interdomain region (CIDR)α1.1 and DC13 CIDRα1.4 domains. IT4var07 CIDRα1.4 inhibited generation of activated protein C (APC) on lung and dermal endothelial cells and blocked the APC–EPCR binding interaction on brain endothelial cells. IT4var19 CIDRα1.1 inhibited thrombin‐induced endothelial barrier dysfunction in lung endothelial cells, whereas IT4var07 CIDRα1.4 inhibited the protective effect of APC on thrombin‐induced permeability. Overall, these findings reveal a much greater complexity of how CIDRα1‐expressing parasites may modulate malaria pathogenesis through EPCR adhesion.